The European Bank for Reconstruction and Development : A Comparative Analysis of the Constituent Agreement - Shihata, Ibrahim F.I., (International Law - Book Archive pre-2000., 1990)
In May 1990, forty countries, together with the European Economic Community and the European Investment Bank, signed the Agreement establishing the European Bank for Reconstruction and Development. This book analyses the Agreement, concentrating on the three main areas relevant to the activities of the EBRD: its financing, its operations, and its organisation and management. The EBRD will be a unique institution, charged with facilitating Eastern Europe's transition to a market economy.